Rapid and accurate diagnosis of brain abscess caused by Nocardia asiatica with a combination of Ziehl‐Neelsen staining and metagenomics next‐generation sequencing. (22nd December 2020) - Huang, T.; Chen, Y.; Zhang, J.; He, R.; Qu, D.; Ye, Q.; Chen, X.
Abstract : Background and purpose: Early and accurate diagnosis is vital in cerebral nocardiosis, a very rare and infectious disease associated with a high mortality rate. Herein, we report a case that a patient with brain abscess was swiftly diagnosed and successfully treated. Methods: We report a case of a 61‐year‐old woman with a brain abscess caused by Nocardia asiatica, diagnosed by a combination of Ziehl‐Neelsen staining and metagenomics next‐generation sequencing (mNGS). Results: A 61‐year‐old woman with left breast cancer resection, diabetes mellitus and a 7‐month discontinuous cough and fever was admitted to our hospital. On the third day of hospitalization, she experienced a sudden loss of consciousness and was diagnosed with a brain abscess and a pathological change in cerebral mass on brain magnetic resonance imaging (MRI). Due to the failure of culturing any microorganisms from the pup, the dissected sample from the patient with Ziehl‐Neelsen staining tested positive for acid‐fast bacilli and was subjected to mNGS. The pathogen was identified as N. asiatica and the patient was treated accordingly with linezolid and trimethoprim‐sulfamethoxazole until complete recovery was confirmed by the follow‐up cerebral MRI. Conclusions: This is the first case report of a brain abscess caused by N. asiatica being swiftly diagnosed by a combination of Ziehl‐Neelsen staining and mNGS. This rapid diagnosis allowed us to successfully treat this rare infection. Abstract : This is the first case report of a brain abscess caused by Nocardia asiatica being rapidly diagnosed by metagenomics next‐generation sequencing in combination with Ziehl‐Neelsen staining. A complete record from an initial consultation to post‐treatment follow‐ups will be beneficial to relevant health professionals.